ACESSO À JUSTIÇA E CUSTAS JUDICIAIS: UMA DICOTOMIA - Caricielli Maisa Longo; Marcelo Pereira Longo (Universidade do Oeste Paulista, 2010)
The study examines the dichotomy between the constitutional guarantee of access to judicial and expenses required by the state judge to conduct the exercise of judicial activity. The collection of high litigation costs and the promise of access to justice are two opposed postures state. Assessing the problem and learned that the provision of legal services to the population becomes an obstacle, because the legal costs is one of the factors that inhibit access to justice.